Thermal Science Example 4-2 - Baskharone, Erian (McGraw-Hill's AccessEngineering., 2013)
This video illustrates how to handle a double leg process with the first leg being a constant-pressure heating process, whereas the second is a constant-volume cooling process?restoring the superheated vapor down to a given pressure.?????????????????????